Modeling, simulation and analysis of a computer controlled car-like vehicle - Saurabh Aggarwal. (2008)
System modeling and simulation are more widely used in robotics and engineering to reduce development time, improve the design and miniaturization of complex systems. This thesis work mainly focuses on complete vehicle modeling and simulation of computer controlled car-like vehicle. It also focuses on complete analysis of various subsystems namely: Driving, Steering and Braking subsystems of the vehicle. This project is a subset of a bigger project, Collaborative Autonomous Robotics System in built up area (CARSysB), which is aimed at creating a multi-agents unmanned surveillance system. Unmanned surveillance brings with a lot of benefits to the user. It not only saves manpower but also reduce the risk involved to the personnel carrying out the manned surveillance therefore there is a great interest in this area.